As Virgens Marias da Nova Espanha e do Arcebispado de Lima durante os séculos XVI e XVII: entre a idolatria e a santidade - Beltramini, Carolina de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The aim of this paper is to analyze two saints named Virgin of Guadalupe, in New Spain, and Our Lady of Copacabana, in the Archdiocese of Lima, that lived during the Colonial Period, between the XVI and XVIII century. We seek to understand how the process of transition from the idolatry to sanctity was made, using colonial chronicles. We noticed that, in Peru as well as in Mexico, these writings followed a narrative pattern, according to the historic period. At first there was a silent period, after that some mentions to the virgins as idolatries and finally the consolidation of the catholic worship to them. We will analyze these processes and the reasons that made them being seen as idolatry and then accepted by the church, and considered catholic saints and symbols of devotion. We believe that the Religious Reformation, the Council of Trent and the Limenses Councils were extremely important ways for this change in the conception of the two virgins in Peru and New Spain. In this way we intend to analyze these processes and understand how they interfered in the writers’ view making possible the consolidation of the sanctity

Este trabalho analisa duas santas durante o período colonial, séculos XVI e XVII. Virgem de Guadalupe na Nova Espanha e Nossa Senhora de Copacabana no Arcebispado de Lima. Buscamos compreender de que forma se deu a transição da idolatria a santidade, através das crônicas coloniais. Notamos que as crônicas, tanto no Peru, quanto no México seguiram um padrão narrativo, de acordo com a época. Houve primeiramente um período de silêncio, logo após pequenas menções as Virgens como idolatrias e por fim a consolidação do culto católico a elas. Analisaremos esses processos e os motivos que fizeram com que as Virgens fossem vistas como idolatria e depois aceitas pela Igreja, consideradas santas católicas e símbolos de devoção. Acreditamos que a Reforma Religiosa, o Concílio de Trento e os Concílios Limenses foram de extrema importância para esta mudança de concepção em relação às Virgens Marias do Peru e da Nova Espanha, pretendemos analisar estes processos e compreender de que maneira eles interferiram nas visões dos cronistas possibilitando a consolidação da santidade
Keywords: História; Idolatria - História; Bispos; História (Teologia); Ídolos e imagens - Culto; Santificação; History